1970
DOI: 10.1111/j.1432-1033.1970.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

The pH 6 Acetolactate‐Forming Enzyme from Serratia marcescens

Abstract: The pH 6 acetolactate-forming enzyme from Serratia mrcescens has been purified to homogeneity, and some of its characteristics have been described.Cocarboxylase and manganese have been completely removed from the enzyme. The addition of FAD to the enzyme did not stimulate the formation of acetolactate, and no FAD was released from the enzyme after trichloro-acetic acid treatment.The enzyme did not crystallize as the same enzyme from Aerobacter aerogenes does, but the kinetic properties of the enzyme are simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
2

Year Published

1973
1973
2001
2001

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 21 publications
0
6
2
Order By: Relevance
“…A sequence that resembles a thiamine PPi-binding site (8) was found in AlsS near the carboxyl terminus; a similar sequence was found at a homologous position in the other proteins; the presence of this putative site is consistent with the mechanism of acetolactate formation (4,17). Thiamine PP1 has been shown to be required by the acetolactate synthase of Serratia marcescens (18), and the acetolactate synthase of Aerobacter aerogenes has been shown to bind TPP (14).…”
Section: Resultsmentioning
confidence: 85%
“…A sequence that resembles a thiamine PPi-binding site (8) was found in AlsS near the carboxyl terminus; a similar sequence was found at a homologous position in the other proteins; the presence of this putative site is consistent with the mechanism of acetolactate formation (4,17). Thiamine PP1 has been shown to be required by the acetolactate synthase of Serratia marcescens (18), and the acetolactate synthase of Aerobacter aerogenes has been shown to bind TPP (14).…”
Section: Resultsmentioning
confidence: 85%
“…This pathway was broadly accepted, up to the 1980s [25,26,27], although the biochemical evidence supporting its existence remained scarce and the 'diacetyl synthase' had never been identified. In another school of thought [28,29] it is assumed that the production of C4 compounds by lactic acid bacteria proceeds in a similar way as found in other organisms such as Bacillus subtilis [30], Klebsiella aerogenes [31], and Serratia marcescens [32]. In this pathway one C5-intermediate, a-acetolactate, is synthesized from two pyruvate molecules and subsequently decarboxylated to acetoin.…”
Section: Pyrmate Metabolismmentioning
confidence: 99%
“…1, we have observed that the first enzyme, the pH 6 acetolactate-forming enzyme, in addition to forming acetolactate from pyruvate, is able to form acetohydroxybutyrate from pyruvate and 2-oxobutyrate [S] . This enzyme requires cocarboxylase and Mn2+ for its activity [6,7] . The second enzyme, acetolactate decarboxylase, decarboxylates acetolactate or acetohydroxybutyrate to yield acetoin or acetylethylcarbinol, respectively [8].…”
Section: Introductionmentioning
confidence: 99%